Ottoman and Dutch merchants in the eighteenth century competition and cooperation in Ankara, Izmir, and Amsterdam - Kadi, Ismail Hakki (Ottoman Empire and its heritage, 2012)
This study analyses the dynamics between the non-Muslim merchant elites of Ankara and Izmir (mostly Greeks and Armenians) and their European competitors in the eighteenth century. In particular, it investigates two major developments: the Dutch attempts to penetrate the mohair trade in Ankara and the local resistance they faced, and the Ottoman non-Muslim merchant's infiltration of the Dutch Levant trade and the Dutch reaction to this form of Ottoman 'expansion'.